2021
DOI: 10.5946/ce.2020.283
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity of Endoscopic Ultrasound-Guided Fine-Needle Aspiration and Endoscopic Ultrasound-Guided Fine-Needle Biopsy in Lymphadenopathy Caused by Metastatic Disease: A Prospective Comparative Study

Abstract: Diagnosing unclear lymphadenopathy such as lymph node metastasis has an enormous impact on the treatment of neoplastic diseases. Therefore, the aim of treatment usually switches from cure to palliation. Numerous other diseases are accompanied by lymphadenopathy, including benign conditions such as infections and inflammatory disease. 1 Hence, sampling of the target node is often required to unveil the underlying diagnosis and to enable adequate clinical management. 2 Intrathoracic or intraabdominal lymphadenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…The results of our EUS-FNA series are in line with the current literature based on studies not using ROSE [ 10 ]. On the other hand, EUS-FNB in our study showed results slightly superior to previous studies, probably due to the prevalent use of newer FNB needles in our series as compared to the large proportion of patients sampled with the reverse bevel needle in previous reports [ 19 , 20 , 23 ].…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…The results of our EUS-FNA series are in line with the current literature based on studies not using ROSE [ 10 ]. On the other hand, EUS-FNB in our study showed results slightly superior to previous studies, probably due to the prevalent use of newer FNB needles in our series as compared to the large proportion of patients sampled with the reverse bevel needle in previous reports [ 19 , 20 , 23 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Sample adequacy analysis showed a non-significant trend in favor of EUS-FNB (96.1% versus 89.5%, p = 0.06), a result consistent with the aforementioned studies [ 19 , 20 ]. As expected, the histological core procurement rate was significantly higher with EUS-FNB (94.2% versus 51.4%; p < 0.001) and this might be of particular relevance in patients with suspected lymphoma, where adequate histological samples are needed for molecular diagnosis and subclassification, as shown in the subgroup of lymphoma patients reported in Table 4 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The diagnosis of malignant lymphadenopaties still relies on excisional biopsy and histological evaluation [2,3]. However, most benign lymphadenopaties may be reliably diagnosed by combining FNC microscopic features with flow cytometry (FC), immunocytochemistry (ICC), microbiological analysis, and molecular testing data [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], thus, avoiding unnecessary diagnostics surgical procedures. Moreover, cytology can be especially useful when a surgery is inadvisable or unfeasible, as in elderly patients with comorbidities or in metastatic settings.…”
Section: Introductionmentioning
confidence: 99%